2013
DOI: 10.3892/ijmm.2013.1344
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal activation of complement C3 in the spinal dorsal horn is closely associated with progression of neuropathic pain

Abstract: The aim of the present study was to investigate the role of complement activation in the pathogenesis of neuropathic pain (NPP) induced by peripheral nerve injury. We modified a classical chronic constriction injury (CCI) model (mCCI), and verified its reliability in rats. Furthermore, reverse transcription-PCR and immunohistochemistry were conducted to investigate complement activation in the spinal dorsal horn and the effect of a complement inhibitor, cobra venom factor (CVF), on the behavior of the mCCI mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 40 publications
2
18
0
Order By: Relevance
“…Our results indicate that the antioxidant enzyme MnSOD is greatly reduced in the ipsilateral side of the spinal cord and sciatic nerve following SNI, in agreement with results from other peripheral nerve injury models, such as sciatic nerve transection and chronic constriction injury (Guedes et al, ; Nie et al, ). Conversely, no modification in the CuZnSOD activity was detected.…”
Section: Discussionsupporting
confidence: 92%
“…Our results indicate that the antioxidant enzyme MnSOD is greatly reduced in the ipsilateral side of the spinal cord and sciatic nerve following SNI, in agreement with results from other peripheral nerve injury models, such as sciatic nerve transection and chronic constriction injury (Guedes et al, ; Nie et al, ). Conversely, no modification in the CuZnSOD activity was detected.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown that the occurrence and development of NPP secondary to peripheral nerve injury is closely associated with the abnormal activation of complements (3,4). Neurons have fewer CRPs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that an abnormal activation of complements in the spinal dorsal horn has an important role in the occurrence and development of NPP secondary to peripheral nerve compression (3,4). In type II diabetic patients with NPP, a biopsy and an immunohistochemical examination of the sural nerve revealed immunoglobulin G (IgG), IgM, C3 and C4 stored in the perineurium and endoneurium.…”
Section: Introductionmentioning
confidence: 99%
“…One of the first complement inhibitors, cobra venom factor (CVF) depletes complement by forming an extremely stable C3 convertase with Bb and rapidly cleaves all available C3 thus depleting the system's ability to initiate further downstream events. CVF administration after induction of either SNL [35] or a modified CCI [37] reversed the established mechanical allodynia. Interestingly, following the animals for a week after full complement depletion indicated that as complement sera activity increased, their mechanical allodynia returned, thus is seems that continuous complement activity is necessary for maintaining the allodynia once established [35,37].…”
Section: Regulationmentioning
confidence: 89%
“…For a variety of peripheral neuropathic injury models including chronic constriction injury (CCI) [37], spared nerve injury (SNI) [7,36], spinal nerve ligation (SNL) [35], sciatic inflammatory neuropathy (SIN) [38,39], partial sciatic nerve injury (pSNI) [40], and chemotherapy induced peripheral neuropathy (CIPN) [31,39] inhibition of complement has been shown to decrease pain behaviors in rodents. It will be relevant here to define experimental measures of pain in animals.…”
Section: Regulationmentioning
confidence: 99%